IMPLEMENTATION OF GEOGRAPHY LEARNING PROGRAM IN FORMING ISLAMIC CHARACTER IN SMA BUKITTINGGI - Syam, Alexander; Lestari, Riri (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This study aims to find out and obtain information about the application of the formulation of a geography learning model that will shape the Islamic character of students in Bukittinggi City by conducting an AHP (Analytical Hierarchy Process) analysis. This type of research is descriptive qualitative using observation, interviews, and documentation in data collection. The types of data used are primary data and secondary data. There are five program priorities that can be applied for development, namely 1) students are accustomed to behaving in a commendable manner and studying hard 2) linking learning with the Al-Quran and Hadith 3) appointing public schools based on Islamic boarding schools 4) facilitating in religious competitions 5) providing provisions for faith and monotheism as early as possible